2019
DOI: 10.1021/acs.nanolett.9b01282
|View full text |Cite
|
Sign up to set email alerts
|

Recognition, Intervention, and Monitoring of Neutrophils in Acute Ischemic Stroke

Abstract: Neutrophils are implicated in numerous inflammatory diseases, and especially in acute ischemic stroke (AIS). The unchecked migration of neutrophils into cerebral ischemic regions, and their subsequent release of reactive oxygen species, are considered the primary causes of reperfusion injury following AIS. Reducing the infiltration of inflammatory neutrophils may therefore be a useful therapy for AIS. Here, inspired by the specific cell–cell recognition that occurs between platelets and inflammatory neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 52 publications
1
71
0
Order By: Relevance
“…The interaction between neutrophil and platelet was involved in the process of vascular injury after ischemic stroke (16). Platelet could facilitate neutrophil recruitment and extravasation into brain parenchyma after stroke, and the amount of infiltrated neutrophil was correlated with stroke progression (17,18). Moreover, high neutrophil-platelet complex formation may increase the risk of stroke in patients with symptomatic carotid stenosis (19).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between neutrophil and platelet was involved in the process of vascular injury after ischemic stroke (16). Platelet could facilitate neutrophil recruitment and extravasation into brain parenchyma after stroke, and the amount of infiltrated neutrophil was correlated with stroke progression (17,18). Moreover, high neutrophil-platelet complex formation may increase the risk of stroke in patients with symptomatic carotid stenosis (19).…”
Section: Introductionmentioning
confidence: 99%
“…Piceatannol is a selective tyrosine kinase inhibitor. Like the CXCL1-soaked sponge, piceatannol, a selective tyrosine kinase inhibitor, can successfully recognize, intervene, monitor, and detach neutrophils into circulation, limiting infiltration of neutrophils in ischemia ( 220 ). Small extracellular vesicles derived from mesenchymal stromal cells protected against BBB disruption, ischemic injury, and neurological dysfunction, specifically by modulating the entry and accumulation of neutrophils ( 221 ).…”
Section: Immunotherapies Targeting Bbb Disruption During Ischemic Strokementioning
confidence: 99%
“…Studies have shown potential curative benefits through alleviating the infiltration of neutrophils [ 102 ]. Inspired by these findings, Tang et al innovatively constructed a platelet membrane coated PLGA nanoplatform with superparamagnetic iron oxide nanoparticles and piceatannol loaded (PTNPs) ( Figure 4 A) [ 103 ]. In their study, the coated platelet membranes facilitated binding between nanoparticles and neutrophils through the recognition of P-selectin (platelet) and PSGL-1 (neutrophil).…”
Section: Cell Membrane Coated Nanoparticle and Its Applications In Cvdsmentioning
confidence: 99%